2016
DOI: 10.1128/jvi.01310-16
|View full text |Cite|
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Viroporin 2B Antagonizes RIG-I-Mediated Antiviral Effects by Inhibition of Its Protein Expression

Abstract: The role of retinoic acid-inducible gene I (RIG-I) in foot-and-mouth disease virus (FMDV)-infected cells remains unknown. Here, we showed that RIG-I inhibits FMDV replication in host cells. FMDV infection increased the transcription of RIG-I, while it decreased RIG-I protein expression. A detailed analysis revealed that FMDV leader proteinase (Lpro), as well as 3C proteinase (3Cpro) and 2B protein, decreased RIG-I protein expression. Lpro and 3Cpro are viral proteinases that can cleave various host proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(137 citation statements)
references
References 53 publications
10
125
0
Order By: Relevance
“…Previous studies have reported that picornaviruses exert various strategies to evade host innate immune responses through certain viral proteins, such as L pro , VP2, VP3, 2A pro , 2C pro , 3A pro , and 3C pro (17,18,(25)(26)(27)(28)(29)(30)(31). In this study, we found that the overexpression of SVV proteins VP2, 3C pro , and 3D reduced Sev-induced IFN-␤ production (Fig.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies have reported that picornaviruses exert various strategies to evade host innate immune responses through certain viral proteins, such as L pro , VP2, VP3, 2A pro , 2C pro , 3A pro , and 3C pro (17,18,(25)(26)(27)(28)(29)(30)(31). In this study, we found that the overexpression of SVV proteins VP2, 3C pro , and 3D reduced Sev-induced IFN-␤ production (Fig.…”
Section: Resultssupporting
confidence: 58%
“…As a result, IFN production and signal transduction are suppressed. FMDV infection restricts the expression of RIG-I, DMA5, and MAVS to attenuate host innate immune responses (18,27,29). FMDV can also target NEMO to cleave it to inhibit NF-B-and IRF3-mediated IFN production (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of house keeping gene glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was also conducted for normalization of total input RNA. Relative transcript levels were calculated by 2 −ΔΔCT (where CT is threshold cycle) method as previously described (Zhu et al, 2016). The primers used in this study were shown in Table 1.…”
Section: Rna Extraction Reverse Transcription and Real-time Pcrmentioning
confidence: 99%
“…Zhu et al observed that RIG-I protein was gradually downregulated as infection progresses (Zhu et al, 2016). Expression of RIG-I inhibited FMDV replication in a dose-dependent manner whereas an enhancement was observed in RIG-I siRNA PK-15 cells.…”
Section: Fmdv Interference With Innate Antiviral Responsesmentioning
confidence: 99%